2003
DOI: 10.1148/radiol.2281020187
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Small Airways in Smokers: Relationship between Air Trapping at CT and Airway Inflammation

Abstract: In smokers, air trapping is correlated with inflammatory infiltration of the smooth muscle layer of small airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
1
36
1
1
Order By: Relevance
“…BARALDO et al [19] found increased numbers of neutrophils and CD8+ cells, but not mast cells, in the small airways of smokers with COPD, and noted that the neutrophil number was inversely related to lung function. This is consistent with an earlier study showing that the number of neutrophils in the ASM bundle in small airways in smokers is related to air trapping determined by computed tomography scanning [45]. In the latter report, there was also a relationship between air trapping, reflecting peripheral obstruction and infiltration of ASM by chymase-positive mast cells.…”
Section: Inflammatory Cell Localisation To Asm Bundlesupporting
confidence: 92%
See 1 more Smart Citation
“…BARALDO et al [19] found increased numbers of neutrophils and CD8+ cells, but not mast cells, in the small airways of smokers with COPD, and noted that the neutrophil number was inversely related to lung function. This is consistent with an earlier study showing that the number of neutrophils in the ASM bundle in small airways in smokers is related to air trapping determined by computed tomography scanning [45]. In the latter report, there was also a relationship between air trapping, reflecting peripheral obstruction and infiltration of ASM by chymase-positive mast cells.…”
Section: Inflammatory Cell Localisation To Asm Bundlesupporting
confidence: 92%
“…Although mast cell density was increased in membranous compared with cartilaginous airway in the epithelium and ASM in one study [12], mast cell numbers were not increased in COPD compared with controls in the proximal airway smooth muscle [39,46] and conflicting data exist for the distal airways. One study showed increased mast cells in the ASM [45] and another reported that numbers were not increased compared with healthy controls [19]. Similarly, T-cells, neutrophils and macrophages (but not eosinophils) have been observed in the ASM in large and small airways in COPD, but only small airway CD8+ T-cells and neutrophils have been shown to be increased compared with healthy controls [19,46].…”
Section: Is the Pattern Of Localisation Of Inflammatory Cells To Airwmentioning
confidence: 99%
“…It also has an advantage for depicting and describing many accompanying pathologic changes in the small and large airways, as well as the parenchyma (17)(18)(19)(20)(44)(45)(46)(47)(48). Furthermore, COPD is not simply a homogeneous, irreversible airflow limitation.…”
Section: Discussionmentioning
confidence: 99%
“…4a) (16). Physiological air-trapping will be detected at an expiratory CT in up to 50% of asymptomatic subjects.…”
Section: Visual Analysismentioning
confidence: 99%